The effect of dimethyl sulfoxide (DMSO) on the removal of Bence-Jones protein and sieving coefficients for various proteins in plasma exchange on multiple myeloma - MIZUNO M.; IKEGAME M.; FUJISHIRO T.; HASEGAWA H.; YANAI T.; KOJIMA K.; 船橋 直樹; OGAWA T; KAWASHIMA S. (Jinko Zoki, 1987)
DMSO was administered in the hope that DMSO will work favourably in removing Bence-Jones protein at plasma exchange (PE) in patient with Bence-Jones type of myeloma. Administering DMSO resulted in a increase in the sieving coefficient (SC) and removal amount of Bence-Jones protein and the filtrated volume increased and rise in TMP was inhibited. SC of other proteins such as β2-MG, Alb and IgG were changed in the extracoporeal method, This suggests that DMSO will also change the separability for the various molecular proteins. The side effects were not seen in our clinical application of DMSO. Bence-Jones型骨髄腫患者の血漿交換(PE)にB-J蛋白をより効率良く除去することを目的に、Dimethyl sulfoxide (DMSO)を投与した。PEはEVAL 2Aをseperatorとする単一膜分離法で1回2lの血漿を置換した。DMSOの投与によりB-J蛋白のsieving caefficient (SC)および総除去量は増加した。同様な結果がrecycle法、oneway法の体外実験にても得られた。Oneway法ではDMSOの投与により、TMPの上昇が抑えられ、また濾液量が増加した。β2-MG、Alb、IgGのSCは、臨床応用およびrecycle法で、DMSOの投与により上昇したが、oneway法ではAlbとIgGのSCは逆に低下した。以上よりDMSOが各蛋白のSeparabibilityについても変化させる可能性が示唆された。尚、DMSOによる副作用は、今回の臨床応用中には一度も認められなかった。